Autologous (T cell depleted) or allogeneic haematopoietic stem cell transplantation for treatment of recalcitrant, severe autoimmune/rheumatic disorders in children?. (29th September 2015) - Abinun, M; Slatter, M; Flood, T; Gennery, A; Hambleton, S; Clark, J; Friswell, M; Foster, H; Cant, A
Abstract : Autologous haematopoietic stem cell transplantation (HSCT) following immunosuppressive conditioning and T cell depletion of the graft is "a valuable option for individual" children with severe autoimmune/rheumatic disease recalcitrant to currently used treatments, although recent evidence of only transient benefit suggest this is not a curative procedure. Potentially curative allogeneic HSCT is "generally not recommended" and unacceptable for the paediatric rheumatology community, even for selected patients at the very severe end of the disease spectrum, as graft-versus-host disease (GVHD) and transplant-related mortality are considered too high a risk.1 Results: Our data on autologous T cell-depleted HSCT in 6 children with juvenile idiopathic arthritis have been recently published2 : four are long-term survivors, three in complete drug-free remission, one relapsed and two died. The authors compare these with the results of allogeneic HSCT in seven children with well-defined, severe and treatment-resistant autoimmune and autoinflammatory diseases: systemic lupus erythematosus (1), immunodysregulation, polyendocrinopathy, enteropathy, X-linked syndrome (3), autoimmune lymphoproliferative syndrome (2), complex periodic fever syndrome due to both mevalonic kinase and TNF-receptor gene mutations (1). Half received HSC from an HLA-matched sibling and half from an unrelated donor; 5/7 received modified myeloablative or reduced intensity conditioning. One child died; 6 achieved remission from their underlying disease: four are cured with 2–6 year follow-up, one with slipping donor chimerism requires further treatment and one is still <1 year post-HSCT. Acute GVHD was frequent but resolved with therapy. Conclusion: The benefit–risk ratio for allogeneic HSCT using contemporary protocols in specialised centres may have surpassed T cell-depleted autologous HSCT for severe autoimmune/rheumatic disease.